A cloud-based MODFLOW service for aquifer management decision support. (May 2015) - Jones, David; Jones, Norm; Greer, James; Nelson, Jim
Abstract: A framework to publish simplified MODFLOW groundwater modeling capabilities to a web interface for use by water managers and stakeholders is presented. Numerical modeling simulations can assist aquifer management decisions, but the amount of time and professional expertise required to wield modern groundwater models often exceeds the resources of regulating agencies – even for simple modeling tasks that are repetitive in nature. The framework is capable of automating such modeling tasks, accepting user input, executing MODFLOW, and generating specialized results including maps and modeling reports. This framework was used to build a pilot system for an aquifer in central Utah, allowing a user to simulate the effects of proposed well diversions. This prototype system allows a user to input properties for any number of candidate wells, execute an associated MODFLOW model, and view drawdown contours and regions of decreased spring flow on a web map interface. The modeling analysis is cast into a geoprocessing workflow using ArcGIS and Arc Hydro Groundwater tools, and then made accessible from a server. Such automated and accessible modeling systems have promising potential to facilitate efficient groundwater resources management and reduce modeling errors. Highlights: We developed a cloud-based tool for running MODFLOW models. The model simulates the impact of proposed changes to groundwater withdrawal permits. The system uses a web interface layered on top of ArcGIS geoprocessing workflows. The code can be customized to support multiple models with different impact criteria. The system allows modeling to be used more extensively in aquifer management.